기후위기 주제 지속가능발전교육 수업 설계와 실행에 있어서 예비과학교사들이 갖는 경험 분석: 상호동료교수법 적용을 중심으로 - 손연아; Son, Yeon-A (대한지구과학교육학회지, 2021)
This study is to implicate for analyzing the expertise of Education for Sustainable Development (ESD) dealing with science-related social issues by reorganizing educational materials on climate crisis topics and analyzing in-depth class performance preparation and actual class by pre-service science teachers. As a result of the study, it was found that pre-service science teachers have the expertise to analyze the curriculum horizontally and extract subject-integrated elements, but it is difficult to perform convergent science classes by incorporating them into the social problem-solving process in actual classes. In addition, it was analyzed that through this study, pre-service science teachers came to think about the importance of having their own specialized expertise when they become school teachers through preparation for their classes integrating science-related social issues. Through the application of the reciprocal peer teaching applied in this study, giving pre-service science teachers of various expertise an opportunity to experience the process of designing and implementing integrated science classes while sharing their expertise will greatly help them improve their convergence education. 이 연구에서는 예비교사들이 기후위기 주제 교육자료를 재구성하고, 상호동료교수법 활용을 통해 팀별로 수업실연 준비와 실제로 수업실연을 하는 과정에서 나타나는 특징을 심층 분석하여, 과학관련 사회 이슈를 다루는 지속가능발전교육 교사 전문성 함양을 위한 시사점을 도출하고자 하였다. 연구결과, 예비과학교사들은 교육과정을 횡적으로 분석하여 교과통합적인 요소를 추출해내는 전문성은 갖추고 있는 것으로 나타났으나, 이를 실제 수업실연을 통해 사회문제해결 과정과 통합시켜 융합적인 과학수업을 실행하는 것에는 어려움을 느끼고 있는 것으로 나타났다. 또한 이 연구를 통하여 예비과학교사들은 상호동료교수법 활용 수업실연 준비 및 경험을 바탕으로 현장과학교사가 되었을 때, 자신만의 특화된 전문성을 갖는 것의 중요성을 생각하게 된 것으로 분석되었다. 이 연구에서 적용한 상호동료교수법 활용을 통해 다양한 전공의 예비교사들이 서로의 전문성을 공유하면서 융합수업 설계와 실행의 과정을 함께 경험할 수 있도록 기회를 주는 것은 예비교사들의 융합교육 교사전문성 향상에 크게 도움이 될 것으로 생각한다.